PENDEKATAN “MIKiR” UNTUK MENINGKATKAN KEAKTIFAN BELAJAR DALAM PEMBELAJARAN ONLINE PADA PERKULIAHAN KIMIA ORGANIK POKOK BAHASAN SENYAWA ALDEHIDA DAN KETON - Sri Mulyanti; Resi Pratiwi; Ana Mardliyah (Orbital: Jurnal Pendidikan Kimia, 2021)
Organic chemistry course is a compulsory subject for chemistry education students. One of the main points of discussion is aldehyde and ketone compounds including the concept of structure, numbering, and nomenclature. With a pandemic condition that demands online lectures, the research team is trying to implement the MIKiR approach online as a solution to making organic chemistry courses interesting, student-centered, and able to achieve learning goals very well. A series of activities with the MIKiR approach have been carried out including introduction, connection, application, and reflection. The results of the evaluation showed that students mastered the concepts of aldehyde and ketone compounds very well with an average value of 80-100%, through a multiple choice test with google form media. After the implementation of the implementation of the MIKiR approach, students were given a questionnaire related to the implementation of lectures, the results of the questionnaire included 59.28% agreeing responses, 32.13% strongly agree, and 8.59% disagree with the implementation of the MIKiR approach in organic chemistry lectures. It can be concluded that the MIKiR approach can be recommended for lecturers in carrying out organic chemistry courses online.